2018
DOI: 10.3390/coatings8090297
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Power on the Interface Microstructure of a Laser Remelting Nano-SiC Modified Fe-Based Ni/WC Composite Coating

Abstract: The plasma sprayed Fe-based Ni/WC composite coating on the surface of 45 steel was post-treated by laser remelting with the addition of nano-SiC. The effect of laser power on the interface microstructure of a laser remelting nano-SiC modified Fe-based Ni/WC composite coatings were researched. The metallographic structure, microscopic morphology, phase composition, and microhardness of the remelted layer were visually analyzed by metallographic microscope, scanning electron microscope (SEM), X-ray diffractomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It can be concluded that the element diffusion phenomenon occurred at the interface between the coating and the substrate after the coupling treatment, mainly Fe and Cr diffused from the substrate to the deep rolling coating, and Ni and W diffused from the coating to the substrate. The interface between the coating and the substrate was clear and in the form of occlusion, and the main bonding mode was mechanical bonding [29,30]. After HT + UDR, the lower part of the coating was embedded with the substrate under the action of temperature field and ultrasonic extrusion pressure, which improves its bonding strength.…”
Section: Organizational Structure Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that the element diffusion phenomenon occurred at the interface between the coating and the substrate after the coupling treatment, mainly Fe and Cr diffused from the substrate to the deep rolling coating, and Ni and W diffused from the coating to the substrate. The interface between the coating and the substrate was clear and in the form of occlusion, and the main bonding mode was mechanical bonding [29,30]. After HT + UDR, the lower part of the coating was embedded with the substrate under the action of temperature field and ultrasonic extrusion pressure, which improves its bonding strength.…”
Section: Organizational Structure Analysismentioning
confidence: 99%
“…Coatings 2023, 13, x FOR PEER REVIEW 7 of 17 occlusion, and the main bonding mode was mechanical bonding [29,30]. After HT + UDR, the lower part of the coating was embedded with the substrate under the action of temperature field and ultrasonic extrusion pressure, which improves its bonding strength.…”
Section: Organizational Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation